2018
DOI: 10.4236/jbise.2018.111001
|View full text |Cite
|
Sign up to set email alerts
|

Would Adding Low Doses of Lithium Salts and/or Prebiotic Fibre Interventions to an Effective Exercise Protocol Further Enhance Retention of Cognitive Integrity? Potential for Preventing Loss of Cognition with Aging Using Combinations of Low Cost Regimens

Abstract: It is clear that loss of cognition is becoming epidemic in our aging society. Onset of dementia and diseases such as Alzheimer's are very prevalent and the prognosis is not optimistic that numbers will decrease in the coming decades. Thus, this epidemic is impacting the quality of life of a large number of people, primarily females, as well as the health care systems of many countries. Of relevance is the fact that large clinical trials of candidate drugs to treat these conditions have not been overwhelming su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Thus, to address the chronicity of some conditions to resist exercise-based interventions may require some pharma interventions to reverse epigenetic modifications contributing to the chronicity or better identification of hormone-dependent targets contributing to post-menopausal risk for cardiovascular conditions and obesity which could lead to targeted pharma interventions. Such interventions do not have to be complicated or expensive, as previously it was suggested that adding low doses of the non-patentable metabolic modulator lithium carbonate and/or prebiotics may enhance the benefits of exercise in relation to cognition (Hart, 2018b ), but it may also be beneficial for other risk factors as well.…”
Section: Can We Improve On Aerobic and Resistance Exercise To Enhance Conditioning Of Physiological Systems?mentioning
confidence: 99%
“…Thus, to address the chronicity of some conditions to resist exercise-based interventions may require some pharma interventions to reverse epigenetic modifications contributing to the chronicity or better identification of hormone-dependent targets contributing to post-menopausal risk for cardiovascular conditions and obesity which could lead to targeted pharma interventions. Such interventions do not have to be complicated or expensive, as previously it was suggested that adding low doses of the non-patentable metabolic modulator lithium carbonate and/or prebiotics may enhance the benefits of exercise in relation to cognition (Hart, 2018b ), but it may also be beneficial for other risk factors as well.…”
Section: Can We Improve On Aerobic and Resistance Exercise To Enhance Conditioning Of Physiological Systems?mentioning
confidence: 99%
“…In contrast, those with advanced disease, with associated pathological disruption of tissue integrity and more extensive epigenetic alterations, would potentially be less likely to exhibit a positive response to exercise than patients in early disease. Furthermore, the use of exercise in conjunction with suitable drugs or compounds, could provide additive or synergistic effects for the exercise component (Hart, 2018c). Secondly, if epigenetic alterations, and not just tissue disruptive pathology, are playing a critical role in the distinction between whether exercise is health vs. medicine, then it may be possible to reverse the epigenetic alterations using drugs or other interventions.…”
Section: The Distinctions Between Exercise Is Health Vs Exercise Is mentioning
confidence: 99%